A review of collective action in rural Ghana - Salifu, Adam; Francesconi, Gian Nicola; Kolavalli, Shashidhara (International Food Policy Research Institute, 2010)
With the beginning of the new millennium and the increasing concerns with regard to wild privatization reforms, African governments, international donors and development scholars have been showing renewed interest in collective action. As a result, farmer-based organization (FBOs) and agricultural cooperatives (agri–coops) are back on the policy agenda for Africa as a preferential means to achieve a more equitable, inclusive and community-driven development of rural areas. The objective of this paper is to provide a snapshot of the patterns and determinants in the development of FBOs and agri–coops in Ghana. With the intention to fill knowledge gaps, harmonize perceptions, update and broaden public understanding of FBOs and agri–coops in Ghana, this review compiles and compares as much secondary evidence as possible and fills in missing evidence through focus group discussions and key informant interviews. The paper concludes with some implications for policy-making and for further and more empirical research.